Pengaruh Volume Penjualan, Harga Jual, dan Biaya Produksi Terhadap Laba Bersih pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar di BEI: Studi Kasus PT Indofood Sukses Makmur Tbk 2021-2023 - Revanda Sabila Putri Romadhony; Sri Murwanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the positive and significant influence of sales volume, selling price, and production costs partially and simultaneously on the net profit of PT Indofood Sukses Makmur Tbk for the 2021-2023 period. This type of research is descriptive with a quantitative approach. The research subject is PT Indofood Sukses Makmur Tbk for the 2021-2023 period. The data used is secondary data in the form of quarterly financial reports for 2021-2023 obtained from documentation techniques. The sampling technique in this study uses non-probability sampling, namely purposive sampling. Data were analyzed using SPSS. The results of this study indicate a positive and significant influence between sales volume on net profit, a positive and significant influence between selling price on net profit, a positive and significant influence between production costs on net profit, and a simultaneous influence of sales volume, selling price, and production costs on net profit.